Wave impact on a rigid and flexible wall using various viscous fluids during sloshing - Korkmaz, Fatih C. (SAGE PUBLICATIONS LTD, 2023)
This paper addresses a study of wave impacts on the chamfered shape of a structure during sloshing, using two different fluids through experimental analysis. Horizontal oscillations are carried out on the tank under various excitation frequencies at a fixed amplitude. Rigid and relatively flexible walls are considered for measuring pressure impact and structural deformation from the wave impacts. Various wave impulses are directed at the sidewall, and the structural deformations are discussed in detail. Wave impacts for various fluids are carried out, from which the pressure-time history, strain values, and free-surface deformation measurements are highlighted. Through the analysis, the breaking wave gets distorted by bottom chamfer at around the vertical portion of the wall. Therefore, physical results are changed likely to having with the wave strike the wall. The impact from more viscous fluids have also been found to reduce both the dynamic pressure and structural strain at practically the same rates in comparison with less viscous fluids.
Keywords: Wave impact; chamfered tank; viscous effect; pressure distribution; strain measurement; PRESSURE; TANK; FORCES; Engineering